Design process in footwear industry using the potential of universal CAD system - Olesya A. Surovtseva (Advanced Engineering Research)
The work objective is to use the capacities of the science-intensive and universal mechanical CAD TP by adapting them to solve complex specialized problems of the footwear process design that will allow industry enterprises transfer to a whole new level of solving design-engineering problems. The theoretical and methodological basis of the study is the theory of complex systems simulation; the operations research theory; the method of system- structural analysis of objects; the classification and coding technique; the methodology of data systems development, databases and knowledgebases creation; the mathematical logic; the method of aprior ranking of factors. On the basis of the standard shoemaking techniques, and similar production techniques used in the modern shoe factories, an aggregate engineering process of the shoes assembly of various construction methods consisting of 310 production steps, each of which is assigned a code, is developed. A list of structuring units characterizing the design-processing footwear specifications is worked out to formalize data on the shoe bottom parts. And the clusters that affect a particular set and operational sequence are allocated within each block. On the basis of the data obtained from the system- structural analysis, structural-logical models of designing the shoes assembly of various construction methods are developed. A schematic form clearly reflects the interrelation logic between the clusters and operational steps. The database “ObuvPro” that allows solving problems on the design process in the shoe factory is developed to ensure the operational, regulatory, and information support for the territorial-production footwear companies.